Cortical Relay Time Shortens in Parkinson's Disease with Apraxia - OĞUZ, SEMRA (JOURNAL NEUROLOGICAL SCIENCES, 2017)
Cortical relay time (CRT) is a neurophysiologic method that measures transmission between sensory and motor cortices. In this study, we calculated CRT to evaluate intrahemispheric transmission in idiopathic Parkinson's disease (PD). We recorded the following parameters: 1) long latency reflexes (LLRs), 2) motor-evoked potentials (MEPs), and 3) somatosensory-evoked potentials (SEPs) according to previously published reports, and cortical relay time was calculated using the following formula: Latency of LLR II - (onset latency of MEP response + latency of N20 response of SEP). CRT was shorter in patients with apraxia compared with patients without apraxia. The findings may raise the possibility of intrahemispheric aberrant conduction or abnormal synaptic reorganization in the presence of apraxia in PD.
Keywords: Apraxia; Parkinson's disease; Cortical relay time; MULTIPLE SYSTEM ATROPHY; LONG-LATENCY REFLEXES; DEFAULT-MODE NETWORK; SENSORIMOTOR CORTEX; DYSFUNCTION; SCLEROSIS